Dendrochemistry: Ecosystem Services Perspectives for Urban Biomonitoring - Semeraro, Teodoro; Luvisi, Andrea; De Bellis, Luigi; Aretano, Roberta; Sacchelli, Sandro; Chirici, Gherardo; Marchetti, Marco; Cocozza, Claudia (Frontiers in Environmental Science, 2020)
The worldwide increase in urban and industrial areas represents a challenge for urban green management, pollutant mitigation and environmental monitoring. We propose an analysis approach for the spatial and spatial-temporal distribution of pollutants in the environment through dendrochemistry techniques, in order to gauge the value of this discipline in urban ecosystem. The proposed analysis models can be useful to evaluate significant changes in space and time related to economic activities and to describe the “impacts” of adopted strategies, as demonstrated in the case study of the opening or closure of factories, and therefore to describe the cause-effect relation connected with human activities. Trees represent a key factor for urban planning, providing a plethora of ecosystem services including in-depth environmental monitoring, which is one of the main elements to be included in a high quality urban design. The proposed approach aims at suggesting the dendrochemistry as a novel and feasible tool definable as a cost-saving ecosystem service in the urban context.